Practicing Contextual Teaching and Learning Approach to Enhance Students’ Higher Order Thinking Skill on Writing Ability - Hakim, Muhammad Wildan; Sari, Dina Merris Maya (Universitas Lancang Kuning, 2022)
Contextual Teaching and Learning (CTL), a learning approach which connects learning materials with real life applications within the context of students’ lives, encourages students to find the meaning of what they have learned on their own and the lecturer only act as a guide or facilitator, so the students are motivated to think critically. This study aims to describe the implementation of CTL approach to enhance students’ higher order thinking skill (HOTS) in writing ability of STKIP PGRI Sidoarjo, which has been found in preliminary observations to be lacking in this aspect. This quantitative research uses a quasi-experimental design through a pretest-posttest pattern. The research sample was 22 students of 2021 A class (Experimental Class) and 23 students of 2021 B class (Control Class). The data were collected through observation, test, and questionnaires. The higher order thinking skill includes: understanding problems (24,20%), making assumptions (28,17%), explaining in depth (25,13%), solving problems (23,25 %), and making conclusions (20,63%). From the table of t-test results, the results (α) = 0.004. It can be stated that (α) < 0.05, so it can be concluded that there is a significant difference in the students' higher order thinking skill in writing ability by using contextual teaching and learning approach. The findings revealed that the contextual teaching and learning approach was successful to enhance students’ higher order thinking skill in writing ability. Moreover, it is recommended that CTL and higher order thinking skill have significant influence toward writing ability.